The Rise of Teaching Specialist Roles in the Legal Academy: Implications and Possibilities - Do, Christina; Ricciardo, Aidan (2020)
The prevalence of teaching specialist academic roles has risen substantially within universities in Australia and abroad over the past decade. This paper explores the perceptions of specialist roles within law schools by presenting the perspectives of four nationally acclaimed legal academics who have received Australian Awards for University Teaching. The paper considers the potential implications that teaching specialist positions may have on the legal academy, offering approaches that law schools can implement to facilitate a successful transition for the academic staff who assume these teaching specialist roles, and ultimately the law schools that employ them. Whilst it is acknowledged some negative implications associated with teaching specialist roles are systemic within the higher education sector, it is contended that to achieve broad cultural and attitudinal change, such change must first occur locally at a school, faculty and institutional level.